Perkembangan dan Struktur Pertumbuhan Ekonomi Sektor Pertanian di Kabupaten Pesisir Selatan - Syahrial Syahrial; Ilham Martadona; Suci Rahmadani (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2022)
The agricultural sector is the dominant business field in the Gross Regional Domestic Product (GRDP) in increasing the economy of Pesisir Selatan Regency. Therefore, this study aims to analyze the economic development of the agricultural sector in Pesisir Selatan District, and to analyze the structure of the economic growth of the agricultural sector in Pesisir Selatan District. The analytical method used is Entropy Diversity Index Analysis (IDE) and Klassen Typology Analysis. The results showed that the three sub-sectors in the agricultural sector, the food, horticulture and plantation sectors in Pesisir Selatan District were still underdeveloped. The structure of the economic growth of the agricultural sector in Pesisir Selatan Regency which is occupied by 15 commodities from the food, horticulture and plantation sub-sectors is included in the developing category by 33 percent, the underdeveloped category by 33 percent, the prime category by 20 percent, and the potential category by 13 percent. The recommendation given is that the government should make policies to increase the productivity of the agricultural sector by conducting counseling and increasing the use of agricultural technology.